ANALYSIS OF THE PROSPECTS FOR THE DEVELOPMENT OF AUTOMATION OF TECHNOLOGICAL PROCESSES IN THE CHEMICAL INDUSTRY - Rahmatov Doniyor Xudoyorovich; Olimbayev Otajon Azamat o’g’li; O’ng’arov Sardor Alisher O’g’li; Omonboyev Kamol Dilmurod o’g’li; O’ngarov Sardorbek Tursunboy o’g’li (Galaxy International Interdisciplinary Research Journal, 2022)
This article discusses the development of automation of technological processes in the chemical industry and its prospects for the future. The chemical industry is one of the most important industries in the Republic of Uzbekistan. The issue of automation of technological processes is an important and integral part of this industrial branch.